OP21 An Economic Evaluation of Non-Communicable Diseases in Brazil. (17th September 2012) - Rtveladze, K; Marsh, T; Brown, M; Webber, L; Kilpi, F; McPherson, F; Levy, D; Conde, W; Monteiro, C
Abstract : Background: Non-communicable diseases are increasingly recognised as the major health issue facing many governments. Brazil has observed a rapid change in the weight profiles of its population, with the prevalence of obesity and overweight increasing partly as a result of the well documented effect of the nutrition transition. Obesity-related diseases are placing a substantial health and economic burden on the country. While the problem has been recognized, the implications of current trends on future overweight and obesity rates, BMI-related disease and costs associated with that disease burden have not been considered. Methods: A previously developed micro-simulation model was used to project through the year 2050 the extent of obesity, BMI related diseases, and associated health care costs in Brazil. A Monte-Carlo simulation method has been utilized to simulated BMI related diseases. In total, thirteen conditions were modelled: coronary heart disease, stroke, hypertension, diabetes, knee osteoarthritis, and eight cancers (breast, kidney, colorectal, oesophageal, endometrial, gallbladder, liver and pancreas). The authors also projected a possible decrease in the BMI and its impact on health and health care costs. Results: In 2010, nearly 45% of the Brazilian male population were overweight or obese (BMI ≥25kg/m²), but by 2050 we project rates as high as 95%. A slightly less pessimistic picture is observed among females: 42% in 2010 increasing to 52% in 2050. The disease incidence figures increase considerably due to obesity patterns. However, BMI reduction across the population will alter these disease projections. Nearly three million diabetes cases and USD 388 million in health care expenditure can be avoided with a five percent reduction in BMI alone by 2050. Conclusion: Obesity rates are rapidly increasing in Brazil creating a high burden of diseases and associated health care costs. However, even a one and percent reduction in prevalence rates will substantially reduce the disease and cost burden. Though some steps have been taken for tackling the obesity problem, Brazil still needs a strong, comprehensive policy involving multiple agencies and institutions with strong leadership.